The following statements <span>demonstrates why the following is a non-example of a polynomial.</span>
1. The expression has a variable raised to a negative exponent.
2. The expression has a variable in the denominator of a fraction.
3. The expression has a variable raised to a fraction.
Answer:
my answer is in the graph. hope i am right!
Step-by-step explanation:
Answer:
4096
Step-by-step explanation:
<em><u>Simplify:</u></em>
=((−4)3)2
=((−4)3)*((−4)3)
=((−4)*(−4)*(−4))*((−4)*(−4)*(−4))
=(−4)*(−4)*(−4)*(−4)*(−4)*(−4)
=(−4)6
<em><u>Step by Step:</u></em>
<u><em>((−4)3)2
</em></u>
<u><em>=(−64)2
</em></u>
<u><em>=4096</em></u>
<u><em /></u>
Answer: 4096
<em><u>Hope this helps.</u></em>
is b because he has been a great friend of the object of his cow and he is very good about the fact he has been coughing all night long time is a force of the object to do the work and to be a good man and
Answer:
3+6×(5+4÷2)-7
Step-by-step explanation:
To solve the expression use order of operations.
Right now the expression solves to:
3+6×5+4÷2-7 6* 5 = 30
3 + 30 + 4÷2-7 4 ÷ 2 = 2
3 + 30 + 2 - 7 Add and subtract left to right.
33 + 2 - 7
35 - 7
28
To make it solve to 38, add parenthesis:
3+6×(5+4÷2)-7 (5+4÷2) = 7
3+6×(7)-7 6*7 = 42
3 + 42 - 7 Add and subtract from left to right
45 - 7
38